Good/Bad, Right/Wrong, and their Analogues - McKenna, William (Investigaciones Fenomenológicas, 2021)
This essay presents an experimental theory of values. An abstract schema is extracted from two pairs of concepts that are used in moral evaluation, good and bad, on the one hand, and right and wrong on the other. The schema is then used to explore the analogues of the moral concepts in aesthetic and epistemic evaluation. Este ensayo presenta una teoría experimental de los valores. Se extrae un esquema de dos pares de conceptos que se utilizan en la evaluación moral: bueno y malo, por un lado, y correcto e incorrecto por el otro. El esquema se usa luego para explorar los análogos de los conceptos morales en la evaluación estética y epistémica.